Automatic Detection of Pulmonary Embolism in CTA Images Using Machine Learning - Ozkan, Haydar; Tulum, Gokalp; Osman, Onur; Sahin, Sinan (Elektronika ir Elektrotechnika, 2017)
In this study, a novel computer-aided detection (CAD) method is introduced to detect pulmonary embolism (PE) in computed tomography angiography (CTA) images. This method consists of lung vessel segmentation, PE candidate detection, feature extraction, feature selection and classification of PE. PE candidates are determined in lung vessel tree. Then, feature extraction is carried out based on morphological properties of PEs. Stepwise feature selection method is used to find the best set of the features. Artificial neural network (ANN), k-nearest neighbours (KNN) and support vector machines (SVM) are used as classifiers. The CAD system is evaluated for 33 CTA datasets with 10 fold cross-validation. The sensitivities of these classifiers are obtained as 98.3 %, 57.3 % and 73 % at 10.2, 5.7 and 8.2 false positives per dataset respectively. DOI: http://dx.doi.org/10.5755/j01.eie.23.1.17585